Cystin genetic variants cause autosomal recessive polycystic kidney disease associated with altered Myc expression - Chaozhe Yang (Nature Portfolio, 2021)
Abstract Mutation of the Cys1 gene underlies the renal cystic disease in the Cys1 cpk/cpk (cpk) mouse that phenocopies human autosomal recessive polycystic kidney disease (ARPKD). Cystin, the protein product of Cys1, is expressed in the primary apical cilia of renal ductal epithelial cells. In previous studies, we showed that cystin regulates Myc expression via interaction with the tumor suppressor, necdin. Here, we demonstrate rescue of the cpk renal phenotype by kidney-specific expression of a cystin-GFP fusion protein encoded by a transgene integrated into the Rosa26 locus. In addition, we show that expression of the cystin-GFP fusion protein in collecting duct cells down-regulates expression of Myc in cpk kidneys. Finally, we report the first human patient with an ARPKD phenotype due to homozygosity for a deleterious splicing variant in CYS1. These findings suggest that mutations in Cys1/CYS1 cause an ARPKD phenotype in mouse and human, respectively, and that the renal cystic phenotype in the mouse is driven by overexpression of the Myc proto-oncogene.